Antimicrobial peptides grafted onto the surface of N-acetylcysteine-chitosan nanoparticles can revitalize drugs against clinical isolates of Mycobacterium tuberculosis - Primo, Laura Maria Duran Gleriani [UNESP]; Roque-Borda, Cesar Augusto [UNESP]; Carnero Canales, Christian Shleider; Caruso, Icaro Putinhon [UNESP]; de Lourenço, Isabella Ottenio [UNESP]; Colturato, Vitória Maria Medalha; Sábio, Rafael Miguel [UNESP]; de Melo, Fernando Alves [UNESP]; Vicente, Eduardo Festozo [UNESP]; Chorilli, Marlus [UNESP]; da Silva Barud, Hernane; Barbugli, Paula Aboud [UNESP]; et al. (Elsevier, 2024)
Tuberculosis is caused by Mycobacterium tuberculosis (MTB) and is the leading cause of death from infectious diseases in the World. The search for new antituberculosis drugs is a high priority, since several drug-resistant TB-strains have emerged. Many nanotechnology strategies are being explored to repurpose or revive drugs. An interesting approach is to graft antimicrobial peptides (AMPs) to antibiotic-loaded nanoparticles. The objective of the present work was to determine the anti-MTB activity of rifampicin-loaded N-acetylcysteine-chitosan-based nanoparticles (NPs), conjugated with the AMP Ctx(Ile21)-Ha; against clinical isolates (multi- and extensively-drug resistant) and the H37Rv strain. The modified chitosan and drug-loaded NPs were characterized with respect to their physicochemical stability and their antimycobacterial profile, which showed potent inhibition (MIC values <0.977 μg/mL) by the latter. Furthermore, their accumulation within macrophages and cytotoxicity were determined. To understand the possible mechanisms of action, an in silico study of the peptide against MTB membrane receptors was performed. The results presented herein demonstrate that antibiotic-loaded NPs grafted with an AMP can be a powerful tool for revitalizing drugs against multidrug-resistant M. tuberculosis strains, by launching multiple attacks against MTB. This approach could potentially serve as a novel treatment strategy for various long-term diseases requiring extended treatment periods.
Keywords: Antimicrobial peptide; Extensively drug-resistant; Mycobacterium tuberculosis; N-acetylcysteine-chitosan